Evi1 Counteracts Anti-Leukemic and Stem Cell Inhibitory Effects of All-Trans Retinoic Acid on Flt3-ITD/Npm1c-Driven Acute Myeloid Leukemia Cells - Nguyen, Chi Huu (Biomedicines, 2020)
All-trans retinoic acid (atRA) has a dramatic impact on the survival of patients with acute promyelocytic leukemia, but its therapeutic value in other types of acute myeloid leukemia (AML) has so far remained unclear. Given that AML is a stem cell-driven disease, recent studies have addressed the effects of atRA on leukemic stem cells (LSCs). atRA promoted stemness of MLL-AF9-driven AML in an Evi1-dependent manner but had the opposite effect in Flt3-ITD/Nup98-Hoxd13-driven AML. Overexpression of the stem cell-associated transcription factor EVI1 predicts a poor prognosis in AML, and is observed in different genetic subtypes, including cytogenetically normal AML. Here, we therefore investigated the effects of Evi1 in a mouse model for cytogenetically normal AML, which rests on the combined activity of Flt3-ITD and Npm1c mutations. Experimental expression of Evi1 on this background strongly promoted disease aggressiveness. atRA inhibited leukemia cell viability and stem cell-related properties, and these effects were counteracted by overexpression of Evi1. These data further underscore the complexity of the responsiveness of AML LSCs to atRA and point out the need for additional investigations which may lay a foundation for a precision medicine-based use of retinoids in AML.